Identification of Ketoprofen Chemical Compounds in Jamu for Menstrual Pain Relief Using Thin-Layer Chromatography Method - Suhaera, Suhaera; Meilanda, Rastria; Basrianshah, Basrianshah; Rachmayanti, Aprilya Sri; Sammulia, Suci Fitriani (Papua Medicine and Health Science, 2024)
Jamu is a traditional form of medicine that should be free from the contamination of medicinal chemicals and only use organic materials from plants or animals. This study aims to detect the presence of Ketoprofen in Jamu for menstrual pain relief using Thin Layer Chromatography (TLC). In this study, TLC was used to identify the presence of medicinal chemicals through spots on the TLC plate. The mobile phase used was a mixture of chloroform and methanol (9:1), with the stationary phase being a silica gel GF 254 nm plate. Detection was performed at UV wavelengths of 254 nm and 365 nm. Six samples were tested, and the results showed that no Ketoprofen was detected in any of the samples, thus the study was not continued with UV-Vis spectrophotometry. The Rf value of the standard comparator was 0.53, while the Rf value of the samples was close to this standard, at 0.73. Based on these results, it can be concluded that all tested Jamu samples for menstrual pain relief do not contain Ketoprofen